Ecovillage Market Segmentation Based on Sustainability Tourism Concept at Panji Village - Andiani, Nyoman Dini; Arismayanti, Ni Ketut; Mahardika, A. A. Ngr Yudha Marthin; Nugraha, Gede Putra (E-Journal of Tourism; Volume 10 Number 2 (September 2023)DO - 10.24922/eot.v10i2.108774, 2023)
Tourism market segmentation needs to be known, as is the case with the development of Tourism Villages. The purpose of this research is to find potential market segmentation that can be targeted for Panji Tourism Village. Qualitative research methods through in-depth interviews were conducted. The data can be processed using the AHP analysis tool. The results show that market segmentation for the ecovillage concept in Panji Tourism Village is the family tourist market share, the main criteria is feasibility which means that the future prospects of developing tourist attractions developed in Panji Tourism Village are tourist activities that can be enjoyed by families, with current considerations looking at a market that has the potential to come for families because apart from easy access and the potential tourist attractions offered can be enjoyed by family members. The results of this study have implications for the readiness of the community to continue to innovate local products that can be enjoyed by tourists of all ages in one family. By continuing to pay attention to the various possible needs of tourists, especially the family tourist market, it is hoped that a sustainable visit will occur . Keywords: tourism; village; market segment.